Positive electrode sheet and lithium-ion battery containing the same

By using ternary positive electrode materials in the positive electrode sheet of lithium-ion batteries and controlling their exothermic enthalpy, micropore volume and particle size change rate, the shortcomings in lithium-ion batteries in terms of safety and energy density are solved, and high energy density and good high temperature safety are achieved.

CN119742312APending Publication Date: 2025-04-01CHINA AVIATION LITHIUM BATTERY LUOYANG
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411920279.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have shortcomings in terms of safety and energy density, especially the high-temperature safety performance of high-nickel ternary cathode active materials is poor, resulting in safety hazards.

Method used

By using ternary positive electrode materials in the positive electrode sheet and comprehensively controlling the exothermic enthalpy value, micropore volume and D(3,2) particle size change rate of the deliquified positive electrode active material, a specific relationship is met to ensure that the lithium-ion battery has good safety and high energy density at high temperatures.

Benefits of technology

It realizes that lithium-ion batteries have a high energy density while maintaining good high temperature safety, which improves the overall performance of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742312A_ABST
    Figure CN119742312A_ABST
Patent Text Reader

Abstract

The present invention discloses a positive electrode plate and a lithium ion battery containing the same, belonging to the field of electrochemical technology. The positive electrode plate of the present invention comprises a positive electrode current collector and a positive electrode active material layer arranged on the surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active material, wherein the positive electrode active material comprises a ternary positive electrode material; the positive electrode plate satisfies the following relationship: -6.0≤27.5×V×10 3 ‑(H×△D 3,2 ) 0.5 / 10≤7.5; wherein V is the micropore volume of the positive electrode active material; H is the exothermic enthalpy value in the range of 80 to 250°C in the differential scanning calorimetry analysis of the positive electrode active material in the 75% delithiation state; △D 3,2 It is the D(3,2) particle size change rate of the positive electrode active material before and after holding the pressure at 35KN for 30s. The lithium ion battery containing the positive electrode sheet of the present invention has a higher energy density while maintaining good high temperature safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a positive electrode plate and a lithium ion battery comprising the same. Background Art

[0002] With the progress of the times and the development of science and technology, the requirements for lithium-ion batteries are getting higher and higher. Lithium-ion batteries not only need to have high energy density, but also need to have long service life and high safety performance. Especially in the field of electric vehicles and large-scale energy storage, the safety requirements for lithium-ion batteries are becoming more and more urgent.

[0003] The lithium iron phosphate system has better safety performance on the market, but its theoretical specific capacity is only about 170mAh / g, and its energy density is too low to meet the actual application needs of passenger cars. The ternary system (NCM) that was developed later has a higher reversible specific capacity, and its weight energy density within the safety limit is about 160-170Wh / kg. Therefore, it is considered to be the most promising power lithium-ion battery. However, the main problem with ternary positive electrode active materials is that their high-temperature safety performance is poor. These shortcomings are more obvious in high-capacity high-nickel ternary positive electrode active materials. For high-nickel ternary positive electrode active materials, nickel ions are mainly Ni 4+ Existence, Ni 4+ It has strong oxidizing properties and can oxidize and decompose the electrolyte, corrode the current collector, and release heat and gas. It is also unstable itself. When the temperature exceeds a certain level, it is easy to thermally decompose and release oxygen, posing a huge safety hazard to the battery system.

[0004] At present, lithium-ion batteries still have many shortcomings in balancing safety and energy density. Many methods to improve the safety of lithium-ion batteries come at the expense of the energy density of lithium-ion batteries, which greatly restricts the development of batteries.

[0005] Therefore, it is necessary to provide a positive electrode plate that has both high temperature safety and high energy density, and a battery using the positive electrode plate. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a positive electrode plate and its application. A lithium-ion battery containing the positive electrode plate has a higher energy density while maintaining good high-temperature safety.

[0007] To achieve the above object, in a first aspect of the present invention, a positive electrode plate is provided, the positive electrode plate comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material, and the positive electrode active material comprising a ternary positive electrode material;

[0008] The positive electrode sheet satisfies the following relationship:

[0009] -6.0≤27.5×V×10 3 -(H×△D 3,2 ) 0.5 / 10≤7.5;

[0010] Where V is the micropore volume of the positive electrode active material, in cm 3 / g, the diameter of the micropores is 2 to 50 nm;

[0011] H is the exothermic enthalpy of the positive electrode active material in the differential scanning calorimetry analysis in the range of 80 to 250°C when the positive electrode active material is in a 75% delithiation state, in J / g;

[0012] △D 3,2 It is the change rate of D(3,2) particle size of the positive electrode active material before and after being pressed at 35KN pressure for 30s, in %.

[0013] As a preferred embodiment of the present invention, the positive electrode sheet satisfies the following relationship: -0.5≤27.5×V×10 3 -(H×△D 3,2 ) 0.5 / 10≤4.0.

[0014] As a preferred embodiment of the present invention, the range of V is 0.3×10 -3 ~0.6×10 -3 cm 3 / g.

[0015] As a further embodiment of the present invention, the range of V is 0.4×10 -3 ~0.5×10 -3 cm 3 / g.

[0016] As a preferred embodiment of the present invention, the range of H is 900 to 2000 J / g.

[0017] As a more preferred embodiment of the present invention, the range of H is 1000 to 1300 J / g.

[0018] As a preferred embodiment of the present invention, the ΔD 3,2 The range is 7 to 15%.

[0019] As a more preferred embodiment of the present invention, the ΔD 3,2 The range is 8.5~11%.

[0020] As a preferred embodiment of the present invention, the chemical formula of the ternary cathode material is LiNi x Co y Mn(1-x-y) O2, where 0.75≤x<1, 0<y≤0.25, 0<x+y<1.

[0021] In a second aspect of the present invention, the present invention provides a lithium-ion battery comprising the positive electrode sheet described above.

[0022] In a third aspect of the present invention, the present invention provides an electronic device comprising the lithium-ion battery described above.

[0023] The beneficial effects of the present invention are:

[0024] The present invention provides a positive electrode plate and a lithium ion battery and an electronic device containing the same. In the positive electrode plate of the present invention, a ternary positive electrode material is used as a positive electrode active material, and by comprehensively controlling the exothermic enthalpy value, micropore volume, and D(3,2) particle size change rate of the de-lithiated positive electrode active material, the lithium ion battery containing the positive electrode plate has a higher energy density while maintaining good high temperature safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is the DSC spectrum of the positive electrode active material of Example 6 of the present invention. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0028] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0029] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.

[0030] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0031] Positive electrode

[0032] An embodiment of the present invention provides a positive electrode plate, the positive electrode plate comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material, and the positive electrode active material comprising a ternary positive electrode material;

[0033] The positive electrode sheet satisfies the following relationship:

[0034] -6.0≤27.5×V×10 3 -(H×△D 3,2 ) 0.5 / 10≤7.5;

[0035] Where V is the micropore volume of the positive electrode active material, in cm 3 / g, the diameter of the micropores is 2 to 50 nm;

[0036] H is the exothermic enthalpy of the positive electrode active material in the differential scanning calorimetry analysis in the range of 80 to 250°C when the positive electrode active material is in a 75% delithiation state, in J / g;

[0037] △D 3,2 It is the change rate of D(3,2) particle size of the positive electrode active material before and after being pressed at 35KN pressure for 30s, in %.

[0038] In the positive electrode plate of the present invention, a ternary positive electrode material is used as the positive electrode active material. By comprehensively controlling the exothermic enthalpy value, micropore volume, and D(3,2) particle size change rate of the de-lithiated positive electrode active material, the lithium-ion battery containing the positive electrode plate has a higher energy density while maintaining good safety.

[0039] For the positive electrode sheet, during the charging and discharging process of the lithium-ion battery, the positive electrode active material in the positive electrode sheet undergoes changes in crystal structure and chemical state due to the embedding and extraction of lithium ions. When the battery is charging, lithium ions flow from the negative electrode (negative electrode active material) to the positive electrode, and the positive electrode active material will embed lithium ions, thereby forming a lithium ion storage state; during the discharge process, lithium ions are released from the positive electrode, and the positive electrode active material will detach from some lithium ions and enter a de-lithiated state.

[0040] In the de-lithiated positive electrode sheet, due to the flow of lithium ions, the structure of the positive electrode active material will change, and the lattice structure may become loose or expanded. When most of the lithium ions in the positive electrode active material are de-intercalated into the negative electrode, a large number of cracks appear in its internal structure. This state is the most unstable state of the positive electrode active material.

[0041] The present invention conducts thermal analysis test on the positive electrode active material in the 75% delithiation state, which can more accurately detect its thermal stability performance. The exothermic enthalpy value of the positive electrode active material reflects the heat released by the positive electrode active material to the outside world within a specific temperature range. Generally speaking, the lower the exothermic enthalpy value of the positive electrode active material in the 75% delithiation state, the better. The lower the exothermic enthalpy value of the positive electrode active material, the better its thermal stability and the lower the risk of thermal runaway.

[0042] The present invention has found that, for lithium-ion batteries, generally speaking, self-heating begins when the temperature reaches 80°C, thereby initiating a series of chemical reactions that release more heat, causing safety hazards. The heat released by the decomposition of the positive electrode active material itself ends at about 250°C, and the exothermic reaction between the negative electrode and the electrolyte begins to occur at a higher temperature. Therefore, the exothermic enthalpy value in the range of 80 to 250°C is selected in this application to actually reflect the working conditions of the positive electrode sheet.

[0043] However, the exothermic enthalpy value of the positive electrode active material should not be too low. As an energy storage material, the energy density of the positive electrode active material is also related to the exothermic enthalpy value. During the test process of differential scanning calorimetry (DSC), the positive electrode active material may undergo certain phase changes or chemical reactions, resulting in certain thermal effects. If the exothermic enthalpy value is too low, it may indicate that the chemical reaction of the positive electrode active material is inactive and the reaction activity is poor. The energy density of the positive electrode sheet is usually related to the reaction activity of the material. In other words, a too low exothermic enthalpy value may mean that the energy density of the material is insufficient, thereby limiting the energy storage capacity of the lithium-ion battery.

[0044] In the present invention, V is the micropore volume of the positive electrode active material, wherein the diameter of the micropore is 2 to 50 nm. The diameter of the micropore can be measured by a nitrogen adsorption specific surface area test method using a micropore distribution measuring device, a Microstar 3020 device.

[0045] For micropores with a diameter of 2 to 50 nm, when the micropore volume is appropriate, the positive electrode sheet can retain an appropriate amount of electrolyte in the lithium-ion battery, so that the positive electrode active material can fully contribute to the charge and discharge reaction, which helps to improve the conductivity of the battery and thus improve the energy density. When the micropore volume is too small, it is difficult for the electrolyte to penetrate between the positive electrode active materials, so the diffusion distance of lithium ions from the positive electrode active materials to the electrolyte increases, which deteriorates the battery conductivity. When the micropore volume is too large, it means that the reaction area between the positive electrode active material and the electrolyte in the electrolyte is too large. Excessive reaction area may increase the interface problems between the positive electrode active material and the electrolyte, such as electrode polarization, increased interface impedance, etc., which may cause the current transmission of the battery to be blocked, thereby affecting the power output of the battery and reducing the energy density of the battery; too large a reaction area may also lead to uneven charge and discharge reactions, increase the local current density in the battery, and generate too much heat in certain areas, thereby causing safety hazards such as thermal runaway of the battery.

[0046] The D(3,2) particle size is the volume surface area average particle size, also known as the Sauter average diameter. It is calculated by dividing each particle size interval percentage by the average value of the corresponding particle size interval and then adding them up. The D(3,2) particle size reflects the average volume distribution of the particulate material. It performs a volume-weighted average of the contributions of large and small particles. Compared with the Dv50 particle size (the particle size corresponding to 50% in the particle volume distribution), the D(3,2) particle size pays more attention to the volume characteristics of the particulate material, especially the outliers in the positive active material particles. Changes in volume distribution may affect the performance and behavior of the material in terms of its electrochemical reaction activity.

[0047] Under the condition of maintaining the pressure at 35KN for 30s, the positive electrode active material is subjected to pressure, and some particles of the positive electrode active material may be squeezed and compressed to a certain extent, and some particles may be broken, resulting in a certain change in the D(3,2) particle size of the positive electrode active material.

[0048] The inventors have found that the D(3,2) particle size change rate of the positive electrode active material before and after holding the pressure at 35KN for 30s can reflect the stability of the positive electrode sheet and the charge and discharge performance. The lower the D(3,2) particle size change rate, the higher the stability of the positive electrode sheet. During the charge and discharge process of the battery, under the influence of the stress generated by the cycle, the positive electrode active material can maintain a high structural stability, which helps the positive electrode sheet to carry out efficient electrochemical reactions, so that the battery maintains excellent energy density and also helps to improve battery safety. However, a certain amount of particle crushing may increase the interface area of ​​the reaction in the battery, which can improve the charge and discharge efficiency of the battery; and the positive electrode active material will undergo a moderate volume change during the battery charge and discharge cycle, which helps to maintain a higher battery capacity. This means that if the D(3,2) particle size change rate is too low, the volume change of the positive electrode active material may be insufficient, which may lead to a limitation in the battery energy density.

[0049] It should be noted that V, H and △D 3,2 There are certain mutual influences and constraints between them. The exothermic enthalpy value of the positive electrode active material is related to the particle size and pore distribution of the positive electrode active material; the D(3,2) particle size change rate of the positive electrode active material is affected by the porosity and pore size distribution of the positive electrode active material. Considering that the micropore volume of the positive electrode active material reflects part of the pore distribution, the size of the micropore volume of the positive electrode active material will also affect the exothermic enthalpy value of the positive electrode active material and the D(3,2) particle size change rate.

[0050] Based on the influence of the micropore volume, D(3,2) particle size change rate and exothermic enthalpy value of the positive electrode active material on battery safety and energy density, the inventors found that when the positive electrode sheet satisfies the relationship: -6.0≤27.5×V×10 3 -(H×△D 3,2 ) 0.5 When / 10≤7.5, the lithium-ion battery containing the positive electrode sheet has excellent safety and energy density.

[0051] Exemplarily, in the present invention, 27.5×V×10 3 -(H×△D 3,2 ) 0.5 The value of / 10 can be -6.0, -5.5, -5.0, -4.0, -3.0, -2.0, -1.0, 0, 1.0, 2.0, 4.0, 6.0, 6.5, 7.0, 7.5, or it can be an interval formed by any two of the above values.

[0052] In one embodiment, the positive electrode plate satisfies the following relationship: -0.5≤27.5×V×10 3 -(H×△D 3,2 ) 0.5 / 10≤4.0.

[0053] When the positive electrode satisfies the above preferred relationship, V, H and △D 3,2 The comprehensive control is relatively more suitable, and the battery containing the positive electrode sheet has higher safety and energy density.

[0054] In one embodiment, the range of H is 900-2000 J / g. For example, the H can be 900 J / g, 950 J / g, 1000 J / g, 1100 J / g, 1300 J / g, 1500 J / g, 1700 J / g, 1900 J / g, 1950 J / g, or 2000 J / g.

[0055] In one preferred embodiment, the range of H is 1000-1300 J / g.

[0056] In addition to the particle size and pore distribution of the positive electrode active material, the exothermic enthalpy of the positive electrode active material is also related to the chemical composition and crystal structure of the positive electrode active material, and the preparation process of the positive electrode sheet will also affect its exothermic enthalpy. The exothermic enthalpy of the positive electrode sheet can be controlled by adjusting the chemical composition, crystal structure, particle size, pore distribution and other parameters of the positive electrode active material and the preparation process of the positive electrode sheet.

[0057] The present invention does not limit the detection of the exothermic enthalpy value, and those skilled in the art can detect the exothermic enthalpy value of the positive electrode active material according to conventional technical means. For example, DSC test can be used for detection.

[0058] It should be noted that, in this article, "x% delithiation state" refers to the state when the molar content of lithium extracted from the positive electrode active material during the charging process of the battery accounts for x% of the theoretical lithium content. In actual use, the positive electrode active material is generally set to a "full charge state" and a "charge cut-off voltage" to ensure the safe use of the battery. "Full charge state" means that the state of charge (State of Charge, SOC) of the secondary battery is 100%. In other words, the lithium-ion battery composed of the positive electrode containing the above-mentioned positive electrode active material is charged to the charge cut-off voltage within the range of reversible charge and discharge. The "full charge state" or "charge cut-off voltage" will vary to a certain extent due to different positive electrode active materials or differences in safety requirements.

[0059] In this paper, the correspondence between "delithiation state" and "voltage" is combined to obtain the positive electrode active material in the "75% delithiation state" for research. Specifically, a series of standard button half-cells are prepared using the positive electrode active material; they are charged to 4.0V, 4.1V, 4.2V, 4.3V, 4.4V, 4.5V, 4.6V, and 4.7V at a rate of 0.1C respectively; then the positive electrode plates of the battery are removed, the electrolyte is removed by washing, and the positive electrode active material is digested; the mass concentration of Li and transition metal (Ni, Co, Mn, etc.) elements of the positive electrode active material is tested by inductively coupled plasma-optical emission spectrometry (ICP-OES) to calculate the "delithiation state", and the corresponding relationship between the charging voltage and the "delithiation state" is obtained, and then the charging voltage corresponding to the "75% delithiation state" is obtained. Then, the button half-cell is charged to the voltage corresponding to the "x% delithiation state", and the positive electrode active material in the "75% delithiation state" can be disassembled to obtain further research. For example, the chemical formula of the positive electrode active material converted at a voltage of 4.4 V is Li 0.25 Ni 0.9 Co 0.07 Mn 0.03 O2, the corresponding delithiation state is (1-0.25)×100%=75% delithiation state, that is, the battery voltage corresponding to the 75% delithiation state is 4.4V.

[0060] In one embodiment, the range of V is 0.3×10 -3 -0.6×10 -3 cm 3 / g, for example, the V may be 0.30×10 -3 cm 3 / g, 0.34×10 -3 cm 3 / g, 0.40×10 -3 cm 3 / g, 0.45×10 -3 cm 3 / g, 0.50×10 -3 cm 3 / g, 0.52×10 -3 cm 3 / g, 0.55×10 -3 cm 3 / g, 0.60×10 -3 cm 3 / g.

[0061] In one preferred embodiment, the range of V is 0.4×10 -3 -0.5×10 -3 cm 3 / g.

[0062] The micropore volume of the positive electrode active material is related to the particle size and shape of the positive electrode active material, the synthesis method of the positive electrode active material (such as too high sintering temperature may lead to the closure or merging of micropores, affecting the micropore volume), the modification method of the positive electrode active material, or the preparation conditions of the positive electrode sheet, such as rolling conditions. In other words, the micropore volume of the positive electrode active material can also be controlled by adjusting the above factors.

[0063] The present invention does not limit the detection of micropore volume, and those skilled in the art can detect the micropore volume of the positive electrode active material according to conventional technical means. For example, a micropore distribution measuring device can be used to measure the micropore volume by a nitrogen adsorption specific surface area test method.

[0064] In one embodiment, the ΔD 3,2 The range is 7-15%. For example, the △D 3,2 It can be 7%, 8%, 10%, 12%, 13%, 14%, or 15%.

[0065] In one preferred embodiment, the ΔD 3,2 The range is 8.5~11%.

[0066] △D 3,2 It is affected by the structural stability, particle size distribution, and regularity of the particle morphology of the positive electrode active material particles, and is also related to the preparation process of the positive electrode sheet, such as the coating conditions and rolling conditions of the positive electrode slurry.

[0067] About △D 3,2 The present invention does not limit the detection method. Those skilled in the art can use conventional technical means to detect the △D 3,2 For detection, for example, a laser particle size analyzer can be used to detect the D(3,2) particle size of the positive electrode active material before and after holding the pressure at 35KN for 30s, and the particle size can be calculated by the following method: △D 3,2 =|(D(3,2) 压前 -D(3,2) 压后 )| / D(3,2) 压前 ×100%.

[0068] In one embodiment, the chemical formula of the ternary cathode material is LiNi x Co y Mn (1-x-y) O2, where 0.75≤x<1, 0<y≤0.25, 0<x+y<1.

[0069] In the present invention, for LiNi x Co y Mn (1-x-y)The preparation method of O2 is not limited, and those skilled in the art can prepare the positive electrode active material according to conventional technical means. Exemplarily, the positive electrode active material precursor and the lithium source are mixed, and sintered and crushed to obtain the positive electrode active material.

[0070] The positive electrode active material precursor may be one or more of oxides, hydroxides and carbonates containing Ni, Co and Mn in a stoichiometric ratio, for example, a hydroxide containing Ni, Co and Mn in a stoichiometric ratio. The positive electrode active material precursor may be obtained by methods known in the art, for example, by coprecipitation, gelation or solid phase method.

[0071] In some embodiments of the present invention, the Ni source includes at least one of nickel sulfate, nickel nitrate, nickel chloride, nickel oxalate or nickel acetate; and / or the Co source includes at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt oxalate or cobalt acetate; and / or the Mn source includes at least one of manganese sulfate, manganese nitrate, manganese chloride, manganese oxalate or manganese acetate; and / or the Li source includes at least one of lithium oxide (Li2O), lithium phosphate (Li3PO4), lithium dihydrogen phosphate (LiH2PO4), lithium acetate (CH3COOLi), lithium hydroxide (LiOH), lithium carbonate (Li2CO3) or lithium nitrate (LiNO3).

[0072] The positive electrode active material precursor and the lithium source can be mixed by a ball mill mixer or a high-speed mixer. The mixed materials are added to an atmosphere sintering furnace for sintering. The sintering atmosphere is an oxygen-containing atmosphere, such as an air atmosphere or an oxygen atmosphere; the sintering temperature can be 600 to 1000° C., and the sintering time can be 5 to 15 hours.

[0073] The pulverization process in the preparation of the positive electrode active material may include grinding pulverization and air flow pulverization. The time of air flow pulverization may be 0.5 to 5 hours, the temperature of air flow pulverization may be room temperature (25±5° C.) to 400° C., and the pressure of air flow pulverization may be 0.5 to 1.5 MPa.

[0074] In addition, the positive electrode active material can also be coated. Specifically, the coating material is coated on the surface of the positive electrode active material by dry coating (high temperature solid phase method), and the surface of the positive electrode active material is partially or completely coated with a coating layer formed by the coating material. The coating layer contains at least one element selected from the following (hereinafter referred to as "coating element"): aluminum (Al), titanium (Ti), tungsten (W), boron (B), phosphorus (P), cobalt (Co), yttrium (Y) and silicon (Si).

[0075] The positive electrode active material layer may further include a conductive agent and a binder in addition to the above-mentioned positive electrode active material.

[0076] The conductive agent is used to provide conductivity in the electrode. Any conductive agent can be used without particular limitation as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. Preferred are carbon materials such as carbon nanofibers, carbon blacks such as acetylene black and Ketjen black, activated carbon, graphite, mesoporous carbon, fullerenes, and carbon nanotubes.

[0077] The binder improves the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Therefore, in the embodiment, the binder suitable for use is a fluorinated polyolefin binder, which may include but is not limited to polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (e.g., carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives.

[0078] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.

[0079] In the present invention, the positive electrode sheet can be prepared according to conventional methods in the art. For example, the positive electrode active material, the conductive agent and the binder are dispersed in a solvent, and the solvent can be N-methylpyrrolidone (NMP) or deionized water to form a uniform positive electrode slurry, and the positive electrode slurry is coated on the positive electrode collector, and after drying, rolling and other processes, the positive electrode sheet is obtained.

[0080] Lithium-ion battery

[0081] An embodiment of the present invention provides a lithium-ion battery, comprising the above-mentioned positive electrode sheet, negative electrode sheet and electrolyte.

[0082] The negative electrode sheet of the present invention comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer comprises a negative electrode active material and may further comprise a conductive agent and / or a binder.

[0083] The present invention has no particular limitation on the negative electrode current collector as long as it has high conductivity without causing adverse chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or an aluminum-cadmium alloy can be used.

[0084] For the negative electrode active material, the embodiments of the present invention do not specifically limit the type of the negative electrode active material, and it can be selected according to actual needs. As an example, the negative electrode active material can be natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiOm (0 < m < 2, such as m = 1), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, lithium titanate with spinel structure Li4Ti5O 12 , one or more of Li-Al alloy and metallic lithium.

[0085] The embodiments of the present invention do not specifically limit the types of the conductive agent and the binder in the negative electrode active material layer, and they can be selected according to actual needs. As an example, the conductive agent is one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; the binder is one or more of styrene-butadiene rubber, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral, water-based acrylic resin and carboxymethyl cellulose. The negative electrode active material layer may also optionally include a thickening agent, such as carboxymethyl cellulose.

[0086] The electrolyte of the present invention can be various electrolytes in the art suitable for electrochemical energy storage devices. The electrolyte includes an electrolyte and a solvent, and the electrolyte usually includes a lithium salt.

[0087] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium bis(oxalato)borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluoro bis(oxalato)phosphate (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP). The concentration of the electrolyte in the electrolyte can be 0.5 to 5 mol / L.

[0088] Specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE). Based on the weight of the electrolyte, the weight content of the solvent can be 70-98%.

[0089] In addition, the electrolyte may further include additives. Specifically, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.

[0090] The electrochemical device may further include a diaphragm, which is located between the positive electrode sheet and the negative electrode sheet, and is used to separate the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from contacting and short-circuiting. The diaphragm may be any material suitable for an electrochemical energy storage device isolation membrane in the art. Specifically, the diaphragm includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fiber.

[0091] Electronic Devices

[0092] An embodiment of the present invention provides an electronic device, comprising the lithium-ion battery described above. The electrochemical device serves as a power supply for the electronic device.

[0093] The electronic device refers to any device that can utilize electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Specifically, it may include but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices may be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles may be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0094] The present invention is further described below with specific embodiments:

[0095] Example 1

[0096] Embodiment 1 provides a lithium ion battery, and the preparation method is as follows:

[0097] (1) Preparation of positive electrode sheet

[0098] (1.1) According to LiNi 0.9 Co 0.07 Mn 0.03 The molar ratio of each element Li, Ni, Co, and Mn in the chemical formula of O2 is respectively weighed nickel sulfate, cobalt sulfate, manganese sulfate, and lithium carbonate, wherein lithium carbonate is slightly excessive. Specifically, the ratio of the molar amount of lithium carbonate to the total molar amount of nickel sulfate, cobalt sulfate, and manganese sulfate (Li / Me) is shown in Table 1;

[0099] (1.2) nickel sulfate, cobalt sulfate and manganese sulfate are dissolved in deionized water respectively, and each metal solution is transported to a reactor through a pipeline to form a mixed metal solution, and nitrogen is introduced as a protective gas. NaOH aqueous solution is added to the mixed metal solution as a precipitant, and ammonia water is added as a complexing agent. The concentration and amount of ammonia water in the solution are adjusted to control the pH of the solution (i.e., the pH of the precursor reaction) to 12.5-12.7, and the reaction is carried out. The time of the precursor reaction is shown in Table 1; the reaction product is filtered and dried at 105° C. to obtain a ternary precursor;

[0100] (1.3) The ternary precursor is mixed with lithium carbonate and sintered in an oxygen-containing atmosphere (oxygen flow rate is 130 m 3 / h), the sintering temperature and time are shown in Table 1;

[0101] (1.4) The sintered material is washed with water, then ground, and then crushed using a jet mill. The crushing time, temperature, and pressure are shown in Table 1. After screening, a ternary positive electrode active material is obtained.

[0102] (1.5) Mix the positive electrode active material, binder (polyvinylidene fluoride), and conductive agent (carbon black) in a mass ratio of 97:1:2, add N-methylpyrrolidone (NMP), and stir under the action of a vacuum mixer until the mixed system becomes a positive electrode slurry with uniform fluidity; evenly apply the positive electrode slurry on the positive electrode collector (aluminum foil); transfer the positive electrode collector coated with the positive electrode slurry to an oven for drying, and then roll and cut it to obtain positive electrode sheets.

[0103] (2) Preparation of negative electrode sheet

[0104] The negative electrode active material (artificial graphite), conductive agent (CNT), thickener (carboxymethyl cellulose, CMC), and binder (styrene-butadiene rubber, SBR) are mixed in a mass ratio of 96:2:1:1, and a negative electrode slurry is made by a wet process using a vacuum mixer. The negative electrode slurry is evenly coated on the negative electrode collector (copper foil), and the negative electrode collector coated with the negative electrode slurry is transferred to an oven for drying, and then rolled and cut to obtain a negative electrode sheet.

[0105] (3) Preparation of electrolyte

[0106] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a weight ratio of 1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0107] (4) Preparation of diaphragm

[0108] A polyethylene (PE) diaphragm coated with ceramic and polyvinylidene fluoride is used.

[0109] (5) Preparation of batteries

[0110] The positive electrode sheet, separator and negative electrode sheet prepared above are wound to obtain a bare cell without liquid injection; the bare cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare cell. After vacuum packaging, standing, forming, shaping, sorting and other processes, a lithium-ion battery is obtained.

[0111] Examples 2 to 16, Comparative Examples 1 to 4

[0112] Examples 2 to 16 and Comparative Examples 1 to 4 respectively provide a lithium ion battery, and the preparation method is similar to that of Example 1, except that when preparing the positive electrode plate, the Li / Me, the reaction time of the precursor, the sintering temperature and time, the gas crushing time, the temperature, and the pressure are controlled as shown in Table 1.

[0113] In addition, in each embodiment and comparative example of the present invention, the micropore volume of the positive electrode active material is adjusted to meet the conditions shown in Table 2 by controlling the coating and rolling conditions of the positive electrode slurry and combining different positive electrode active materials.

[0114] Table 1

[0115]

[0116] For each embodiment and comparative example, the micropore volume (V) of the positive electrode active material, the particle size change rate (ΔD) of the positive electrode active material before and after holding the pressure at 35KN for 30s 3,2), in the differential scanning calorimetry analysis of the positive electrode active material in the 100% delithiation state, the exothermic enthalpy value (H) in the range of 80 to 250°C is detected as shown in Table 2. The detection methods of the above items are as follows:

[0117] V: dismantle the lithium-ion battery to obtain the positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 60 minutes, take it out, and dry it at room temperature with a humidity of ≤15%; wash it repeatedly for 3 times to remove the residual electrolyte, scrape the positive electrode active material layer on the surface of the current collector with a ceramic knife, and calcine it at 450°C for 3 hours to remove the conductive agent and the binder to obtain the positive electrode active material;

[0118] Take the positive electrode active material sample to be tested, place it in a 0.1Mpa vacuum environment, and heat it at 200℃ for 2h. Use the Micromeritics Tristar3020 nitrogen adsorption surface area tester to test it. Set the equipment to count the micropore volume of micropores with a diameter of 2 to 50nm, in cm 3 / g;

[0119] △D 3,2 : Disassemble the lithium-ion battery to obtain the positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 60 minutes, take it out, and dry it at room temperature with a humidity of ≤15%; scrape off the positive electrode active material layer on the surface of the current collector, and calcine it at 500°C for 3 hours to remove the conductive agent and the binder to obtain the positive electrode active material;

[0120] The positive electrode active material was dispersed in a 3% sodium hexametaphosphate dispersant solution, and after continuous stirring with a glass rod for 10 turns, all the samples were quickly poured into the particle size distribution instrument test sample pool for testing to obtain the D(3,2) particle size before pressure holding, recorded as D(3,2) 压前 ;

[0121] Take the same mass of positive electrode active material and use a powder compactor to hold the positive electrode active material under a pressure of 35KN for 30 seconds; take out the positive electrode active material after holding the pressure and test it again using the particle size tester according to the above method to obtain the D(3,2) particle size after holding the pressure, which is recorded as D(3,2) 压后 ;

[0122] The △D of the positive electrode active material can be calculated. 3,2 :△D 3,2 =|(D(3,2) 压前 -D(3,2) 压后 )| / D(3,2) 压前 ×100%,△D 3,2 The unit is %.

[0123] H: The lithium-ion battery is charged at a rate of 0.1C to 4.0V, 4.1V, 4.2V, 4.3V, 4.4V, 4.5V, 4.6V, and 4.7V, respectively; the positive electrode sheet of the battery is then removed, and the positive electrode sheet is used as a test sample. The original electrolyte is removed by repeated immersion and cleaning with DMC, and the positive electrode active material is digested to obtain the positive electrode active material; the mass concentration of Li, Ni, Co, Mn, and O elements in the positive electrode active material is tested by inductively coupled plasma-optical emission spectrometry (ICP-OES) to calculate the "delithiation state", and then the positive electrode sheet in the "75% delithiation state" is obtained;

[0124] The above-mentioned positive electrode sheet in the "75% delithiation state" was dried in the glove box, the positive electrode active material layer on the surface of the current collector was scraped off, and calcined at 500°C for 3 hours to remove the conductive agent and binder, and the positive electrode active material in the 75% delithiation state was obtained. DSC detection was performed to obtain the exothermic enthalpy value of the positive electrode active material in the range of 80-250°C. The specific conditions of DSC were: starting from room temperature, heating at a heating rate of 10k / min, heating to 320°C, then stopping heating, the equipment naturally cooled to room temperature, and the test ended. During the test, N2 was used as the purge gas and protective gas, with flow rates of 40ml / min and 60ml / min, respectively.

[0125] Figure 1 This is the DSC spectrum of the positive electrode active material of Example 6. It can be seen that its exothermic enthalpy value in the range of 80 to 250° C. is 1877 J / g.

[0126] Table 2

[0127]

[0128] The performance of the lithium-ion batteries prepared in the above embodiments and comparative examples was tested. The specific items and methods are as follows. The results are shown in Table 3.

[0129] (1) Energy density:

[0130] In a 25°C constant temperature box, the lithium-ion battery was fully charged at 1C and then discharged at 1C. After the discharge was completed, the discharge capacity of the lithium-ion battery was calculated.

[0131] The surface area S of the positive electrode active material layer and the total thickness T of the positive electrode active material layer in the prepared positive electrode sheet were measured. The reversible capacity C (mAh / cm 2 ) = discharge capacity of lithium-ion battery / surface area S of positive electrode active material layer; ratio of reversible capacity per unit area of ​​positive electrode active material to total thickness of positive electrode active material layer C / T (mAh / cm 3 ) = reversible capacity per unit area of ​​the positive electrode active material layer C / total thickness T of the positive electrode active material layer.

[0132] The volume energy density of a lithium-ion battery is measured by the ratio C / T of the reversible capacity per unit area of ​​the positive electrode active material to the total thickness of the positive electrode active material layer.

[0133] (2) High temperature storage volume expansion rate:

[0134] At 25°C, the lithium-ion battery was charged at a constant current of 0.5C to a voltage of 4.2V, and then charged at a constant voltage of 4.2V to a current of 0.05C. The initial volume of the lithium-ion battery at this time was tested by the water displacement method and recorded as V0. The lithium-ion battery was then placed in a constant temperature box at 80°C for 21 days. After the storage, it was taken out and the volume of the lithium-ion battery was tested again by the water displacement method and recorded as V1. 15 lithium-ion batteries were tested in each group and the average value was taken.

[0135] The volume expansion ratio (%) of the lithium-ion battery after storage at 80°C for 21 days = (V1-V0) / V0×100%.

[0136] (3) Nail penetration test pass rate:

[0137] The lithium-ion battery stored at 80°C for 21 days was charged at a constant current rate of 0.05C to a voltage of 4.50V (i.e., full charge voltage), and then charged at a constant voltage of 4.50V to a current of 0.025C (cut-off current) to fully charge the lithium-ion battery, and record the appearance of the lithium-ion battery before the test. The battery was tested in an environment of 25±3°C, with a steel nail diameter of 4mm, a puncture speed of 30mm / s, and a nail position located at the geometric center of the lithium-ion battery plane. The test was stopped after 3.5min or when the surface temperature of the electrode assembly dropped to 50°C. 25 lithium-ion batteries were grouped together to observe the state of the lithium-ion battery during the test. The lithium-ion battery was judged to have passed the nail test if it passed 20 out of 25 nail tests.

[0138] Table 3

[0139]

[0140]

[0141] For the lithium-ion batteries prepared in the embodiments of the present invention, the energy density is ≥500mAh / cm 3 , up to 672mAh / cm 3 , and after being stored at 80℃ for 21 days, the volume expansion rate is ≤20%, and the nail penetration test pass rate is ≥80%, which has excellent high temperature safety performance.

[0142] From Examples 6 to 9 for Examples 1 to 5, and Examples 10 to 16 for Examples 1 to 5, it can be seen that when the D(3,2) particle size change rate, micropore volume, and exothermic enthalpy value of the positive electrode active material meet the preferred range of the present invention, or the positive electrode sheet meets 27.5×V×10 3 -(H×△D 3,2 ) 0.5 When the value of / 10 is -0.5 to 4.0, the energy density and high-temperature safety performance of the lithium-ion battery are relatively more balanced, and the overall performance is better.

[0143] According to the test results of Comparative Examples 1 to 4, when the positive electrode sheet is 27.5×V×10 3 -(H×△D 3,2 ) 0.5 When the value of / 10 is outside the range of -6.0 to 7.5, the lithium-ion battery containing the positive electrode sheet cannot achieve both high energy density and good safety performance.

[0144] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode active material layer comprises a positive electrode active material, wherein the positive electrode active material comprises a ternary positive electrode material; The positive electrode sheet satisfies the following relationship: -6.0≤27.5×V×10 3 -(H×△D 3,2 ) 0.5 / 10≤7.5; Where V is the micropore volume of the positive electrode active material, in cm 3 / g, the diameter of the micropores is 2 to 50 nm; H is the exothermic enthalpy of the positive electrode active material in the differential scanning calorimetry analysis in the range of 80 to 250°C when the positive electrode active material is in a 75% delithiation state, in J / g; △D 3,2 It is the change rate of D(3,2) particle size of the positive electrode active material before and after being pressed at 35KN pressure for 30s, in %.

2. The positive electrode sheet according to claim 1, characterized in that: The positive electrode sheet satisfies the following relationship: -0.5≤27.5×V×10 3 -(H×△D 3,2 ) 0.5 / 10≤4.

3. The positive electrode sheet according to claim 1, characterized in that: The range of V is 0.3×10 -3 ~0.6×10 - 3 cm 3 / g.

4. The positive electrode sheet according to claim 3, characterized in that: The range of V is 0.4×10 -3 ~0.5×10 - 3 cm 3 / g.

5. The positive electrode sheet according to claim 1, characterized in that: The range of H is 900-2000 J / g.

6. The positive electrode sheet according to claim 5, characterized in that: The range of H is 1000-1300 J / g.

7. The positive electrode sheet according to claim 1, characterized in that: The ΔD 32 The range is 7 to 15%.

8. The positive electrode sheet according to claim 7, characterized in that: The ΔD 3,2 The range is 8.5~11%.

9. The positive electrode sheet according to claim 1, characterized in that: The chemical formula of the ternary cathode material is LiNi x Co y Mn (1-x-y) O2, where 0.7≤x<1, 0<y≤0.3, 0<x+y<1.

10. A lithium ion battery, characterized in that: A positive electrode sheet comprising the positive electrode sheet according to any one of claims 1 to 9.

11. An electronic device, characterized in that: A lithium ion battery comprising the lithium ion battery according to claim 10.

Citation Information

Cited By

  • Long-circulation ternary positive electrode material and preparation method and application thereof

    CN121546053A

  • Long cycle ternary positive electrode material and preparation method and application thereof

    CN121546053B